5(2x-2)+5=5-5(5-3x)

Simple and best practice solution for 5(2x-2)+5=5-5(5-3x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(2x-2)+5=5-5(5-3x) equation:


Simplifying
5(2x + -2) + 5 = 5 + -5(5 + -3x)

Reorder the terms:
5(-2 + 2x) + 5 = 5 + -5(5 + -3x)
(-2 * 5 + 2x * 5) + 5 = 5 + -5(5 + -3x)
(-10 + 10x) + 5 = 5 + -5(5 + -3x)

Reorder the terms:
-10 + 5 + 10x = 5 + -5(5 + -3x)

Combine like terms: -10 + 5 = -5
-5 + 10x = 5 + -5(5 + -3x)
-5 + 10x = 5 + (5 * -5 + -3x * -5)
-5 + 10x = 5 + (-25 + 15x)

Combine like terms: 5 + -25 = -20
-5 + 10x = -20 + 15x

Solving
-5 + 10x = -20 + 15x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-15x' to each side of the equation.
-5 + 10x + -15x = -20 + 15x + -15x

Combine like terms: 10x + -15x = -5x
-5 + -5x = -20 + 15x + -15x

Combine like terms: 15x + -15x = 0
-5 + -5x = -20 + 0
-5 + -5x = -20

Add '5' to each side of the equation.
-5 + 5 + -5x = -20 + 5

Combine like terms: -5 + 5 = 0
0 + -5x = -20 + 5
-5x = -20 + 5

Combine like terms: -20 + 5 = -15
-5x = -15

Divide each side by '-5'.
x = 3

Simplifying
x = 3

See similar equations:

| 7y+6=15 | | 2y+x=47 | | 5x-24=51 | | m-5+m+m+3+((m+3)/2)=66 | | 1000/i=600/(i-0.03) | | 4k/5+3=11 | | 2x+(4x+1)+3x+(4x+1)= | | 4k/5+5=11 | | 0.5y+11.4=0.6y+9.9 | | 8m^2+s^2=2tfors | | 30-7x=2+15 | | 30-7x=2+156 | | 7-9x=18-16x | | -0.025y+34.7=0.375y+27.7 | | 4t+23=11t+2 | | 1.2k+2.9=0.5k+7.4 | | 8a+3=3(4+a) | | In(2x)+in(x)=in(8x) | | 2500y+55000=2000y+62000 | | 53=8w+5 | | 8m^2+s^2=2t | | 53=8+5 | | 4t=1o-t | | 1200m+1000=1175m+1500 | | 12.50+.40e=14.75+.25c | | 0.1y=0.2x+1 | | 3.5g+2=3.25g+5 | | 19+45= | | .20p+7=.30p+5 | | 6m+200=-6m+5.00 | | .99d=.89d+10 | | k^4+5*k^3+5*k^2-5*k-6=0 |

Equations solver categories